1912 Vt. Acts and Resolves 310, No. 237, §1. - (:unkn) unknown (My University, 1912)
A person who manufactures, sells, or uses, or possesses with intent to sell or use, an appliance known as or used for a gun silencer shall be fined twenty-five dollars for each offense. This act shall not prevent the use or possession of gun silencers for military purposes when so used or possessed under proper military authority and restriction.
Keywords: SUPPRESSORS